2003
DOI: 10.1080/00498250310001615771
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic analysis of factors determining elimination pathways for sulfate and glucuronide metabolites of xenobiotics II: Studies with isolated perfused rat liver

Abstract: 1. To elucidate the determining factors for elimination pathways of sulfate and glucuronide metabolites of xenobiotics, a single-pass perfusion of 4-methylumbelliferone (4MU) or p-nitrophenol (pNP) was performed with an isolated rat liver preparation. 2. Without bovine serum albumin in the perfusion system, clearance calculated based on the unbound concentration in the liver clearly showed that the net efflux clearances (CLeff) of sulfates from the sinusoidal membrane were much higher than those of glucuronide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…Furthermore, the higher hepatic concentration of 4MUG than 4MUS was generated by much lower CL eff of 4MUG than that of 4MUS (Higaki et al 2003) as well as a higher capacity for glucuronidation than that of sulfation (Benet et al 1995), whereas CL b is comparable between 4MUG and 4MUS (Higaki et al 2003). These results obviously reveal that the sinusoidal efflux must be one of the most important factors for determining the elimination pathways of both conjugates.…”
Section: Resultsmentioning
confidence: 66%
See 3 more Smart Citations
“…Furthermore, the higher hepatic concentration of 4MUG than 4MUS was generated by much lower CL eff of 4MUG than that of 4MUS (Higaki et al 2003) as well as a higher capacity for glucuronidation than that of sulfation (Benet et al 1995), whereas CL b is comparable between 4MUG and 4MUS (Higaki et al 2003). These results obviously reveal that the sinusoidal efflux must be one of the most important factors for determining the elimination pathways of both conjugates.…”
Section: Resultsmentioning
confidence: 66%
“…The reason why CL eff of 4MUS increased might be the non-linearity of the efflux of 4MUS, that is to say, the sinusoidal efflux of 4MUS would already be saturated under normal condition because the hepatic concentration of 4MUS is much higher than that in the presence of NaN 3 . Our previous study also showed that CL eff of 4MUS decreased with the increase in hepatic concentration of 4MUS (Higaki et al 2003). f T for both conjugates also decreased due to very low hepatic concentrations of both conjugates.…”
Section: Resultsmentioning
confidence: 79%
See 2 more Smart Citations
“…The liver single-pass perfusion study was performed following the methods reported by Mortimore with some modifications (21). Briefly, the bile duct and portal vein were cannulated with polyethylene tubes, SP10: i.d.…”
Section: Isolated Liver Single-pass Perfusion Studymentioning
confidence: 99%